EDUKASI KESEHATAN TENTANG PEMANFAATAN DAN EFEK SAMPING OBAT HERBAL UNTUK PENGOBATAN GEJALA TUBERKULOSIS - roisah, roisah (JURNAL PENGABDIAN KEPADA MASYARAKAT SISTHANA, 2025)
Tuberculosis is still a health problem in the community, regular treatment can minimize transmission, and the combination of herbal medicine with anti-tuberculosis drugs can reduce tuberculosis symptoms. Currently, the community does not understand herbal medicine for the treatment of tuberculosis symptoms. Health education is needed for information about the benefits and impacts of herbal medicine in the treatment of tuberculosis. The purpose of this community service is to provide information to families as a companion to the use of herbal medicine for the treatment of tuberculosis symptoms. This community service uses a participatory Action Research (PAR) approach. This approach allows for active interaction with the community. This community service uses lecture and discussion methods for families at risk of tuberculosis, education is given with a time of 1 (one) meeting with a duration of 60 minutes. The media used are leaflets and booklets to make it easier for families to understand herbal medicine. The results obtained after health education were carried out were an increase in family understanding of the benefits and side effects of using herbal medicine for the treatment of tuberculosis symptoms. It is hoped that health education can provide information about the use and side effects in the treatment of tuberculosis symptoms. Keywords: Health education, Herbal Medicine, Tuberculosis